Gamifying Human Circulatory System: A Game-Based Learning Application to Enhance Students' Understanding and Retention of Human Body Concepts For Grade 6 Students - Ambrona, Jan Patrick E.; Esleta, Moses John D; Parayno, Kristian Carlo A (IC-ITECHS, 2024)
This thesis developed a gamified mobile learning application designed to enhance Grade 6 students' understanding of circulatory system concepts namedGamifying Human Circulatory System . Acknowledging the rising significance of games in fostering children's engagement in educational pursuits, this research capitalized on the trend by developing a mobile game that not only captures students' interest but also facilitates the comprehension of complex anatomical concepts. Utilizing a pretest-posttest design with paired t-tests for analysis and survey questionnaires based on the ISO 25010 standards , the study reveals a highly significant positive impact on students' knowledge scores. The Gamifying Human Circulatory System application successfully engaged students, transforming the learning of fundamental circulatory system principles into an enjoyable and effective educational experience. These findings underscored the potential of gamified approaches to create an immersive and entertaining educational environment for Grade 6 students. This study provided valuable insights into science education, emphasizing the practical application of gamification to enhance both engagement and comprehension. Focused on the circulatory system, the study supported the idea that gamified learning tools, particularly in the form of mobile games, can positively influence how young learners interact with scientific concepts. The study's outcome demonstrated that incorporating gamified elements into educational tools holds promise in significantly improving students' understanding, making the learning process both informative and enjoyable in the Grade 6 Science curriculum.